2013
DOI: 10.1088/0004-637x/766/1/9
|View full text |Cite
|
Sign up to set email alerts
|

An Ultraviolet Investigation of Activity on Exoplanet Host Stars

Abstract: Using the far-UV (FUV) and near-UV (NUV) photometry from the NASA Galaxy Evolution Explorer (GALEX), we searched for evidence of increased stellar activity due to tidal and/or magnetic star-planet interactions (SPI) in the 272 known FGK planetary hosts observed by GALEX. With the increased sensitivity of GALEX, we are able probe systems with lower activity levels and at larger distances than what has been done to date with X-ray satellites. We compared samples of stars with close-in planets (a < 0.1 AU) to tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 70 publications
(104 reference statements)
6
56
2
Order By: Relevance
“…The discovery paper (Anderson et al 2012) has found a 16-day rotational modulation and weak Ca ii H+K for the host star. A recent study led by Shkolnik (2013) furthermore derived a high far-UV fractional luminosity log(L FUV /L bol ) = −4.546 ± 0.079 based on the NASA Galaxy Evolution Explorer (GALEX) measurements. The possible absence of high-altitude absorbers would indicate that there is no strong thermal inversion.…”
Section: Near-infrared Thermal Emission From the Dayside Atmosphere Omentioning
confidence: 99%
“…The discovery paper (Anderson et al 2012) has found a 16-day rotational modulation and weak Ca ii H+K for the host star. A recent study led by Shkolnik (2013) furthermore derived a high far-UV fractional luminosity log(L FUV /L bol ) = −4.546 ± 0.079 based on the NASA Galaxy Evolution Explorer (GALEX) measurements. The possible absence of high-altitude absorbers would indicate that there is no strong thermal inversion.…”
Section: Near-infrared Thermal Emission From the Dayside Atmosphere Omentioning
confidence: 99%
“…It has been speculated that similar effects, albeit on a weaker scale, may occur for stars with Hot Jupiters (Cuntz et al 2000;Lanza 2008). Observational studies have been performed on individual systems (Shkolnik et al 2005(Shkolnik et al , 2008Pillitteri et al 2011;Miller et al 2012) as well as on larger samples of planet-hosting stars (Kashyap et al 2008;Poppenhaeger et al 2010;Shkolnik 2013), finding weak correlations of stellar activity with the presence of Hot Jupiters. Indications for higher v sin i values have also been reported (Pont 2009) for systems with Hot Jupiters compared with systems hosting smaller or more distant planets, NASA Sagan Fellow yielding first indications of a tidal influence of exoplanets on their host stars.…”
Section: Introductionmentioning
confidence: 99%
“…As a striking counterexample, the extreme WASP-18 system, which contains a ≃ 10M Jup planet in a 0.94 d period, shows no evidence for planet-linked activity (Miller et al 2012;Pillitteri et al 2014b); such interaction must be either absent, only rarely present, or 8 We ignore the distinction between M P and the minimum mass of explanets derived from radial velocity work, since the sin i inclination term is unknown for most of these systems but provides a typical correction of only ∼15% (Wright & Gaudi 2013). rendered inefficient by an extremely weak stellar magnetic field 9 Shkolnik et al 2013; but see also Miller et al 2012).…”
mentioning
confidence: 99%